Patterns of biofilm production and antiseptic resistance in multidrug-resistant Acinetobacter baumannii clinical isolates - Ušjak, Dušan; Bošković, Lidija (Archives of Pharmacy, 2024)
Acinetobacter baumannii is a notorious pathogen known for its extensive drug resistance and ability to form biofilms, making infections difficult to treat and control. This study investigated antibiotic resistance profiles, biofilm production, and environmental adaptability of 32 A. baumannii clinical isolates. Predominantly hospital-derived, the isolates showed a high proportion of antimicrobial drug resistance, with 93.75% classified as extensively drug-resistant (XDR), and the rest as multidrug-resistant (MDR). Notably, isolates demonstrated high resistance to amikacin and meropenem (MIC50 >4096 μg/mL and 64 μg/mL, respectively). Biofilm production analysis revealed 13 strong producers, 14 moderate, 4 weak, and 1 non-producer. Strong and moderate biofilm producers exhibited higher antibiotic resistance on average. The most favorable conditions for biofilm formation proved to be in glucose-supplemented BHI and at room temperature. Six selected strong biofilm producers displayed significant variability in biofilm production across different media and temperatures. In antiseptic and topical antibiotic persistence tests, isolates showed varied survival and biofilm production, with some thriving and enhancing biofilm in saline and boric acid. The findings emphasize the adaptability and resilience of A. baumannii in clinical settings, highlighting the challenges in treating biofilm-associated infections.
Keywords: Acinetobacter baumannii; biofilm production; antibiotic resistance; antiseptics; environmental adaptability